2006
DOI: 10.1541/ieejeiss.126.1009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Network Programming with Reinforcement Learning and Its Application to Making Mobile Robot Behavior

Abstract: A new graph-based evolutionary algorithm called "Genetic Network Programming (GNP)" has been proposed. GNP represents its solutions as graph structures which have some distinguished abilities. For example, GNP can memorize past action sequences in the network flow and make compact structures. However, conventional GNP is based on evolution, i.e., after GNP programs are carried out to some extent, they are evaluated and evolved based on their fitness values, so many trials must be executed again and again. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The experimentally obtained results demonstrated that their method presents advantages over conventional methods based on GP and EP. Moreover, Chen et al [20] combined GNP with Sarsa learning [21] for stock market trading to judge the timing of buying and selling. The experimentally obtained simulation results obtained using stock price datasets of 16 brands during four years clarified that the fitness and profits of their composed method were higher than the existing stock prediction methods.…”
Section: Related Studiesmentioning
confidence: 99%
“…The experimentally obtained results demonstrated that their method presents advantages over conventional methods based on GP and EP. Moreover, Chen et al [20] combined GNP with Sarsa learning [21] for stock market trading to judge the timing of buying and selling. The experimentally obtained simulation results obtained using stock price datasets of 16 brands during four years clarified that the fitness and profits of their composed method were higher than the existing stock prediction methods.…”
Section: Related Studiesmentioning
confidence: 99%
“…State of the art in this research can be seen that the integration of RL to Evolutionary Algorithms (EA), such as Genetic Algorithm (GA) [6][7][8], Genetic Programming (GP) [9][10][11] and Genetic Network Programming (GNP) [12] were studied in many researches [13][14][15][16][17], where the integration can improve the performance as shown in GNP with RL (GNP-RL) which was implemented to navigate the mobile robot [18]. EA has the evolving ability for capturing the environment using selection, crossover and mutation, while the integration of RL to EA improves the adaptability to the dynamic environments.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed navigation system of the mobile robot in this paper is based on GNP, where GNP has advantages [12] such as (1) re-usability of the nodes which make the structures more compact and (2) applicability to Partially Observable Markov Decision Problem (POMDP). Compared to the other methods, such as Evolutionary Neural Network (ENN) and GP, GNP has better performance [12,18]. Here, GNP with Two-Stage Reinforcement Learning (GNP-TSRL) to face inexperienced changes of the environments was studied.…”
Section: Introductionmentioning
confidence: 99%
“…It is also a broad class of optimal control methods based on estimating value functions from experience, simulation, or search [12]. The RL has been used in many robotics domains, such as autonomous control [13,14], robot soccer [15], behavior making [16], multiagents coordination [17], path planning, etc. In mobile robot path planning, the RL is usually integrated with other approaches, such as neural network (NN), supervised learning (SL), and cerebellar model articulation controllers (CMACs).…”
Section: Introductionmentioning
confidence: 99%